Adhesive composition, adhesive structure, and method for producing adhesive structure
Patent Information
- Application Number
- JP2023142027
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-01
- Publication Date
- 2025-03-13
AI Technical Summary
【0011】 本発明によれば、2枚の無機部材を接着したときに、短時間で接着強度を向上できる接着性組成物、ならびに、その接着性組成物を用いた接着構造体および接着構造体の製造方法を提供することができる。
Smart Images

Figure 2025035163000001 
Figure 2025035163000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesive composition, an adhesive structure, and a method for producing an adhesive structure. [Background technology]
[0002] Patent Documents 1 to 3, for example, describe techniques relating to adhesives for bonding inorganic members such as metals.
[0003] Patent Document 1 discloses a two-part acrylic adhesive composition comprising (1) a polymerizable monomer having a (meth)acryloyl group, (2) a polymerization initiator, (3) a reducing agent, (4) a polymer containing polyorganosiloxane and polyalkyl (meth)acrylate, and (5) an elastomer soluble in the (meth)acrylic acid ester monomer, wherein the polymer containing polyorganosiloxane and polyalkyl (meth)acrylate is capable of swelling with the polymerizable monomer having a (meth)acryloyl group. It also discloses that the two-part acrylic adhesive composition quickly cures at room temperature, thereby allowing members to be fixed in a short time, and that even in this case, the adhesive strength is excellent, making it possible to produce a bonded body having excellent adhesive strength in a short time.
[0004] Patent Document 2 discloses a curable resin composition containing 100 parts by mass of (A) a (meth)acrylate monomer, 1 to 50 parts by mass of (B) an elastomer, 1 to 50 parts by mass of (C) a bismaleimide compound, 1 to 50 parts by mass of (D) a poly(meth)acrylate having one or more radically polymerizable functional groups per molecule, 5 to 100 parts by mass of (E) a compound containing an alkylene oxide chain and having two or more radically polymerizable functional groups per molecule, 0.1 to 10 parts by mass of (F) a polymerization initiator, and 0.01 to 10 parts by mass of (G) a curing accelerator. The patent document describes that the curable resin composition has both high shear adhesive strength and peel adhesive strength even after exposure to heat, and has excellent adhesion to adherends.
[0005] Patent Document 3 discloses an adhesive set comprising a first liquid containing a polymerization initiator and a second liquid containing a reducing agent, wherein at least one of the first liquid and the second liquid further contains (meth)acryloylmorpholine as a monomer, and describes that the adhesive set has excellent rapid curing properties at room temperature, and a method for manufacturing a structure using the adhesive set is provided. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2020-026507 A [Patent Document 2] JP 2018-172565 A [Patent Document 3] Patent Publication No. 2021-024910 Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention provides an adhesive composition that can improve the adhesive strength in a short period of time when bonding two inorganic members together, as well as a bonded structure using the adhesive composition and a method for producing the bonded structure. [Means for solving the problem]
[0008] The present inventors have conducted extensive research to achieve the above object. As a result, they have found that a two-part adhesive composition contains a radical polymerizable monomer (A), a polymerization initiator (B), and a reducing agent (C), the first part contains the radical polymerizable monomer (A) and the polymerization initiator (B), the second part contains the radical polymerizable monomer (A) and the reducing agent (C), and the adhesive composition contains a component (X) having a structural unit derived from butadiene, thereby improving the adhesive strength in a short time when two inorganic members are bonded together, and have completed the present invention.
[0009] According to the present invention, there are provided an adhesive composition, an adhesive structure, and a method for producing an adhesive structure, which are described below.
[0010] [1] A two-part adhesive composition comprising: A method for producing a polymerization reaction system comprising: a radical polymerizable monomer (A); a polymerization initiator (B); and a reducing agent (C); the first agent contains the radical polymerizable monomer (A) and the polymerization initiator (B), the second agent contains the radical polymerizable monomer (A) and the reducing agent (C), The adhesive composition comprises a component (X) having a structural unit derived from butadiene. [2] The adhesive composition according to [1], wherein the content of the component (X) is 1 part by mass or more and 80 parts by mass or less when the total amount of the adhesive composition is 100 parts by mass. [3] The adhesive composition according to [1] or [2], wherein the component (X) contains a radical polymerizable monomer (X1) having a structural unit derived from butadiene. [4] The adhesive composition according to [3], wherein the number of the structural units derived from butadiene in the radical polymerizable monomer (X1) is 10 or more and 70 or less. [5] The adhesive composition according to any one of [1] to [4], wherein the component (X) contains an elastomer (X2) having a structural unit derived from butadiene. [6] The adhesive composition according to [5], wherein the elastomer (X2) comprises one or more selected from the group consisting of butadiene rubber, (meth)acrylonitrile-butadiene rubber, and styrene-butadiene rubber. [7] The adhesive composition according to any one of [1] to [6], wherein the radical polymerizable monomer (A) includes a urethane (meth)acrylate and a polyfunctional (meth)acrylate. [8] The adhesive composition according to [7], wherein the urethane (meth)acrylate has a structural unit derived from the butadiene. [9] The adhesive composition according to [7] or [8], wherein the polyfunctional (meth)acrylate has three or more (meth)acryloyl groups.
[10] The adhesive composition according to any one of [7] to [9], wherein the content of the polyfunctional (meth)acrylate is 1 part by mass or more and 90 parts by mass or less when the content of the radical polymerizable monomer (A) is 100 parts by mass.
[11] The adhesive composition according to any one of [7] to
[10] , wherein the urethane (meth)acrylate has two (meth)acryloyl groups.
[12] The adhesive composition according to any one of [7] to
[11] , wherein the content of the urethane (meth)acrylate is 1 part by mass or more and 80 parts by mass or less when the content of the radical polymerizable monomer (A) is 100 parts by mass.
[13] The adhesive composition according to any one of [1] to
[12] , wherein the radical polymerizable monomer (A) contains a highly polar monomer.
[14] The adhesive composition according to
[13] , wherein the highly polar monomer comprises (meth)acrylic acid.
[15] The adhesive composition according to
[13] or
[14] , wherein the content of the highly polar monomer is 1 part by mass or more and 50 parts by mass or less when the content of the radical polymerizable monomer (A) is 100 parts by mass.
[16] The adhesive composition according to any one of [1] to
[15] , wherein the content of the radical polymerizable monomer (A) is from 70 mass % to 99 mass % based on the total amount of the adhesive composition.
[17] The adhesive composition according to any one of [1] to
[16] , wherein the content of the polymerization initiator (B) is 0.1 parts by mass or more and 20 parts by mass or less, relative to 100 parts by mass of the radical polymerizable monomer (A).
[18] The adhesive composition according to any one of [1] to
[17] , wherein the content of the reducing agent (C) is 0.01 parts by mass or more and 10 parts by mass or less, relative to 100 parts by mass of the content of the radical polymerizable monomer (A).
[19] Using a B-type viscometer, the temperature was 25°C and the shear rate was 0.6 s -1 The adhesive composition according to any one of [1] to
[18] , wherein the viscosity of the first part and the second part, as measured by a viscosity measuring method, is 30 mPa·s or more and 2000 mPa·s or less.
[20] Using a B-type viscometer, the temperature was 25°C and the shear rate was 5.9 s -1 The adhesive composition according to any one of [1] to
[19] , wherein the viscosity of the first part and the second part, as measured by a viscosity measuring method, is 20 mPa·s or more and 2000 mPa·s or less. [twenty one] The adhesive composition according to any one of [1] to
[20] , which has a tensile shear strength T(1) of 0.01 MPa or more as measured in accordance with the following <Tensile shear strength>. <Tensile shear strength> A 20 mm range from the end of a cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) with a width of 25 mm, length of 100 mm, and thickness of 1.6 mm is sandblasted with alumina having a grain size of F150 at a processing pressure of 0.4 MPa and a gun / cold-rolled steel plate distance of 3 cm, and the surface of the sandblasted area is washed with acetone and then left to stand at 23° C. for 30 minutes to prepare two test pieces. Next, the first agent of the adhesive composition is applied to the sandblasted area of one of the test pieces to a thickness of 20 μm to prepare test piece 1, and the second agent is applied to the sandblasted area of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, the test piece 1 and the test piece 2 are bonded together one minute after application of the first agent so that the bonded area is 25 mm × 12.5 mm, the bonded portion is clamped with two modern pinches, and the test piece 1 is fixed in a vice. Next, the modern pinches are removed 20 seconds after bonding, and 30 seconds after bonding, the test piece 2 is pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value of the mechanical force gauge is read, and this value is the tensile shear strength T(1) (MPa). [twenty two] The adhesive composition according to any one of [1] to
[21] , which is capable of bonding inorganic members to each other. [twenty three] An adhesive structure in which two or more inorganic members are adhered to each other, An adhesive structure comprising the inorganic members and a cured product of the adhesive composition according to any one of [1] to
[22] between the inorganic members. [twenty four] A method for producing a bonded structure, comprising the steps of: The adhesive composition is used to bond inorganic members to each other to obtain a bonded structure, The adhesive composition according to any one of [1] to
[22] above is a method for producing an adhesive structure. [twenty five] The bonding step includes: A method for producing a bonded structure as described in
[24] , comprising a step of bonding a first agent-coated surface of the inorganic member to which the first agent has been applied and a second agent-coated surface of the inorganic member to which the second agent has been applied. Effect of the Invention
[0011] According to the present invention, it is possible to provide an adhesive composition that can improve the adhesive strength in a short period of time when bonding two inorganic members together, as well as a bonded structure using the adhesive composition and a method for manufacturing a bonded structure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] Hereinafter, an embodiment of the present invention will be described in detail.
[0013] In this specification, unless otherwise specified, the expression "X to Y" in the explanation of a numerical range means from X to Y. For example, "1 to 5 mass %" means "from 1 mass % to 5 mass %". In this specification, the content of each component represents the content relative to the total content of the first and second agents. In the description of groups (atomic groups) in this specification, when a description is made without specifying whether the group is substituted or unsubstituted, the description includes both groups having no substituents and groups having a substituent. For example, an "alkyl group" includes not only an alkyl group having no substituents (unsubstituted alkyl group) but also an alkyl group having a substituent (substituted alkyl group). In this specification, the term "(meth)acrylic" refers to a concept that includes both acrylic and methacrylic. The same applies to similar terms such as "(meth)acrylate."
[0014] [Adhesive composition] The adhesive composition of the present embodiment is a two-part adhesive composition, and contains a radical polymerizable monomer (A), a polymerization initiator (B), and a reducing agent (C). The first part contains the radical polymerizable monomer (A) and the polymerization initiator (B), and the second part contains the radical polymerizable monomer (A) and the reducing agent (C). The adhesive composition contains a component (X) having a structural unit derived from butadiene.
[0015] As an example of bonding inorganic members together, for example, a rotor in an automobile motor is formed by stacking steel plates, and the steel plates need to be temporarily fixed together with an adhesive until the laminate is finally completely fixed by caulking. In order to enable a process in which an adhesive is applied to several steel plates and then the steel plates are bonded together at once, a two-component adhesive may be used as the adhesive here. However, it may be difficult to achieve adhesive strength in a short time after bonding the steel plates to which the two-component adhesive has been applied. Therefore, when bonding inorganic members together using a two-component adhesive, it may take a long time to transport or convey the bonded items, or to proceed to the next process. As a result of extensive investigations, the present inventors have found that when an adhesive composition contains a component (X) having a structural unit derived from butadiene, the adhesive strength is improved even when two inorganic members coated with the adhesive composition are bonded together and bonded for a short period of time. The reason for this is not clear, but it is believed that because the adhesive composition contains structural units derived from butadiene, even if the first and second parts of the adhesive composition are exposed to oxygen in the air after being applied to inorganic members and before being bonded together, the effect of oxygen on the components in the adhesive composition can be reduced. Therefore, even when bonding is performed in a short period of time, a decrease in the curing rate can be suppressed, and an adhesive strength sufficient to withstand transportation, etc. can be achieved.
[0016] The adhesive composition of the present embodiment can be used, for example, as an adhesive composition used for temporary fixing before a process in which inorganic members are finally and completely fixed to each other.
[0017] <Component (X) Having a Structural Unit Derived from Butadiene> The adhesive composition of the present embodiment contains a component (X) having a structural unit derived from butadiene. When the first and second agents of the adhesive composition are applied to two inorganic members, respectively, and the two inorganic members are bonded together, radicals are generated by mixing the first and second agents, causing an initiation reaction and a propagation reaction. At this time, peroxy radicals with low propagation activity are generated by the oxygen contained in the adhesive, and the curing speed is significantly reduced. On the other hand, when the radical polymerizable monomer (A) contains a monomer having a structural unit derived from butadiene, the peroxy radicals abstract the allylic hydrogen of butadiene and generate carbon radicals with high propagation activity, so that the decrease in the curing speed can be suppressed, and thus, when two inorganic members are bonded, the adhesive strength can be improved in a short time.
[0018] The component (X) having a structural unit derived from butadiene may contain a radical polymerizable monomer (X1) having a structural unit derived from butadiene. The radical polymerizable monomer (X1) is included in the radical polymerizable monomer (A).
[0019] Furthermore, the component (X) having structural units derived from butadiene may contain an elastomer (X2) having structural units derived from butadiene. The elastomer (X2) will be described later.
[0020] The content of the component (X) having a structural unit derived from butadiene in the adhesive composition, when the total amount of the adhesive composition is taken as 100 parts by mass, is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, even more preferably 8 parts by mass or more, and is preferably 80 parts by mass or less, more preferably 60 parts by mass or less, even more preferably 50 parts by mass or less, even more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less. By having the content of the component (X) having a structural unit derived from butadiene within the above range, the influence of oxygen during the period from coating the first and second parts of the adhesive composition on two inorganic members to bonding the two inorganic members can be reduced, and the decrease in the curing speed when the inorganic members are bonded can be suppressed. Furthermore, when the two inorganic members are bonded, the adhesive strength can be improved in a short time.
[0021] <Radical polymerizable monomer (A)> The adhesive composition of the present embodiment contains a radical polymerizable monomer (A). The radically polymerizable monomer (A) preferably includes a urethane (meth)acrylate and a polyfunctional (meth)acrylate. This brings the number of crosslinking groups in the radically polymerizable monomer (A) into an appropriate range, and when two inorganic members are bonded together, the adhesive strength can be improved in a short period of time, and the physical properties of the resulting bonded structure can be improved.
[0022] A polyfunctional (meth)acrylate refers to a compound having two or more carbon-carbon double bonds such as a (meth)acryloyl group, however, polyfunctional (meth)acrylates do not include those that fall under the category of highly polar monomers described below. The polyfunctional (meth)acrylate of the present embodiment preferably contains 3 or more (meth)acryloyl groups, more preferably 4 or more (meth)acryloyl groups, even more preferably 5 or more (meth)acryloyl groups, even more preferably 6 or more (meth)acryloyl groups, and preferably contains 10 or less (meth)acryloyl groups, more preferably 9 or less (meth)acryloyl groups, even more preferably 8 or less (meth)acryloyl groups, and even more preferably contains 7 or less (meth)acryloyl groups. By having the number of (meth)acryloyl groups in the polyfunctional (meth)acrylate be equal to or greater than the lower limit, more crosslinking groups are formed in the radical polymerizable monomer (A), and when two inorganic members are bonded together, the adhesive strength can be improved in a short time. Also, by having the number of (meth)acryloyl groups in the polyfunctional (meth)acrylate be equal to or less than the upper limit, the number of crosslinking groups in the radical polymerizable monomer (A) can be kept within an appropriate range, and variations in physical properties due to poor reaction of the (meth)acryloyl groups can be suppressed.
[0023] As the polyfunctional (meth)acrylate, a polyfunctional (meth)acrylate having an aliphatic chain structure can be used. Examples of polyfunctional (meth)acrylates having an aliphatic chain structure include one or more selected from the group consisting of isocyanuric acid ethylene oxide modified tri(meth)acrylate, pentaerythritol tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolpropane propylene oxide modified tri(meth)acrylate, trimethylolpropane ethylene oxide modified tri(meth)acrylate, diglycerol ethylene oxide modified (meth)acrylate, tris[(meth)acryloyloxyethyl]isocyanurate, ditrimethylolpropane tetra(meth)acrylate, dimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, pentaerythritol ethoxy tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, and dipentaerythritol hexa(meth)acrylate. Among the polyfunctional (meth)acrylates, it is preferable to use a polyfunctional acrylate from the viewpoint of further improving the curing speed of the adhesive composition.
[0024] Among these, it is preferable to use a polyfunctional (meth)acrylate having an aliphatic chain structure, it is more preferable to use one or more selected from the group consisting of dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate, and trimethylolpropane tri(meth)acrylate, it is even more preferable to use one or two selected from the group consisting of dipentaerythritol pentaacrylate and dipentaerythritol hexaacrylate, and it is even more preferable to use dipentaerythritol hexaacrylate. As commercially available products of polyfunctional (meth)acrylate, DPHA M402 manufactured by Toagosei Co., Ltd., TMPT-M manufactured by Shin-Nakamura Chemical Co., Ltd., and the like can be used.
[0025] The content of the polyfunctional (meth)acrylate in the adhesive composition, relative to the content of the radical polymerizable monomer (A) taken as 100 parts by mass, is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, even more preferably 8 parts by mass or more, even more preferably 15 parts by mass or more, even more preferably 25 parts by mass or more, even more preferably 35 parts by mass or more, even more preferably 45 parts by mass or more, even more preferably 55 parts by mass or more, and is preferably 90 parts by mass or less, more preferably 85 parts by mass or less, preferably 80 parts by mass or less. By making the content of the polyfunctional (meth)acrylate equal to or greater than the lower limit, a larger number of crosslinking groups are formed in the radical polymerizable monomer (A), and when two inorganic members are bonded together, the adhesive strength can be improved in a short time. Also, by making the content of the polyfunctional (meth)acrylate equal to or less than the upper limit, the adhesive composition can be prevented from curing too quickly, and the variation in physical properties due to poor reaction of the (meth)acryloyl group can be suppressed, and the coatability can be improved.
[0026] The urethane (meth)acrylate is a compound having a urethane bond and a (meth)acryloyl group. When the radical polymerizable monomer (A) contains a urethane (meth)acrylate, the viscosity of the adhesive composition can be adjusted to a more appropriate range, and thus the coatability can be further improved. The urethane (meth)acrylate preferably has two (meth)acryloyl groups, which allows the number of crosslinking groups in the radical polymerizable monomer (A) to be within an appropriate range, and when two inorganic members are bonded together, the adhesive strength can be improved in a short time, and the coatability can be improved.
[0027] (A) Urethane (meth)acrylate refers to a urethane (meth)acrylate having a urethane bond in the molecule, which is obtained, for example, by reacting (for example, polycondensation reaction) a polyol compound (hereinafter represented by X), an organic polyisocyanate compound (hereinafter represented by Y), and a hydroxy(meth)acrylate (hereinafter represented by Z). Examples of the polyol compound (X) (hereinafter, sometimes simply referred to as polyol) include polyether type and polyester type. The polyol may be a polyhydric alcohol. Among the polyols, one or more selected from polybutadiene having hydroxyl groups at both ends, neopentyl glycol, tetramethylene glycol, butanediol, hexanediol, and polyester polyol are preferred, and one or more selected from polybutadiene having hydroxyl groups at both ends and tetramethylene glycol are more preferred. Examples of the polybutadiene having hydroxyl groups at both ends include polyols having a 1,2-polybutadiene structure. As the organic polyisocyanate compound (Y) (hereinafter sometimes simply referred to as isocyanate), for example, aromatic, aliphatic, cyclic aliphatic, alicyclic, etc. polyisocyanates can be used. Among the isocyanates, one or more selected from toluene diisocyanate (TDI), isophorone diisocyanate (IPDI), diphenylmethane diisocyanate (MDI), hexamethylene diisocyanate (HMDI), and hydrogenated diphenylmethane diisocyanate (hydrogenated MDI) are preferred, and one or two selected from toluene diisocyanate and isophorone diisocyanate are more preferred. The hydroxy(meth)acrylate (Z) (hereinafter sometimes simply referred to as hydroxy(meth)acrylate) is preferably a hydroxyalkyl(meth)acrylate. Among the hydroxyalkyl (meth)acrylates, those represented by formula (1) are preferred. Formula (1) ZO-(R 1 -O-)pH (Wherein, Z is a (meth)acryloyl group, R 1 represents an alkylene group, and p represents an integer of 1 to 10. R in formula (1) 1 The alkylene group preferably has 1 to 8 carbon atoms, and more preferably has 2 to 6 carbon atoms. Among the hydroxyalkyl (meth)acrylates, one or more selected from 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and 4-hydroxybutyl (meth)acrylate are preferred, with 2-hydroxyethyl (meth)acrylate being more preferred. The urethane (meth)acrylate can be produced, for example, according to the descriptions in JP-A-7-25957, JP-A-2002-173515, JP-A-7-292048, JP-A-2000-351819, and the like.
[0028] As the urethane (meth)acrylate, commercially available products can be used. Examples of commercially available products include the following: U-200PA, UA-W2, UA-W2A, UA-122P, UA-160TM, UA-2235PE, UA-4200, UA-4400, UA-7000, UA-31F, UA-7100, U-2HA, U-2PPA, U-6LPA, U-10PA, U-10HA, UA-33H, UA-53H, UA-32P, UA-1100H, etc. manufactured by Shin-Nakamura Chemical Co., Ltd. Articles UN-350, UN-352, UN353, UN-1255, UN-2600, UN-2700, UN-5500 UN-5590、UN-5507、UN-6060PTM、UN-6060S、UN6200、UN-6202、UN-6303、U N-6304、UN-6305、UN-7600、UN-7700、UN-9000PEP、UN-9200A、UN-3320H A、UN-3320HC、UN-3320HS、UN-904、UN-906S、UN-901T、UN-905、UN-952。 Examples: AH-600, UA-306H, UA-306T, UA-306I, UA-510H, UF-8001G, DAUA-167, BPZA-66 MIWON China、Miramer PU210、Miramer PU256、Miramer PU2050、Miramer PU2100、Miramer PU2300C、Miramer PU2560、Miramer PU320、Miramer PU340、Miramer PU3000、Miramer PU3200、Miramer PU3450、Miramer PU5000、Miramer PU610、Miramer PU6510、Miramer PU9500、Miramer PU9800、Miramer UA5216、Miramer SC2100、Miramer SC2152、Miramer SC2404、Miramer SC2565、Miramer MU3603、Miramer PU370、Miramer PU640、Miramer PU2421NT。 EBECRYL 210, EBECRYL 220, EBECRYL 4500, EBECRYL 230, EBECRYL 270, EBECRYL 280 / 15IB, EBECRYL 284, EBECRYL 4491, EBECRYL 4683, EBECRYL 4858, EBECRYL 8307, EBECRYL 8402, EBECRYL 8411, EBECRYL 8413, EBECRYL 8804, EBECRYL 8807, EBECRYL 9270, EBECRYL 7735, KRM8961, EBECRYL 8800, EBECRYL 1259, 294 / 25HD, EBECRYL 4100, EBECRYL 4220, EBECRYL 4513, EBECRYL 4740, EBECRYL 4820, EBECRYL 8311, EBECRYL 8465, EBECRYL 9260, EBECRYL 8701, EBECRYL 8667, EBECRYL 8701, KRM 8667, KRM 8296, EBECRYL 4587, EBECRYL 4200, EBECRYL 4666, EBECRYL 4680, EBECRYL 8210, EBECRYL 8405, KRT 8528, EBECRYL 1290, EBECRYL 5129, EBECRYL 8254, EBECRYL 8301R, KRM 8200, KRM 8200AE, KRM 8530, KRM 8904, KRM 8531BA, KRM 8452, etc. manufactured by Daicel Ornex Co., Ltd. CN910, CN959, CN963, CN964, CN965, CN966, CN969 NS, CN980 NS, CN981 NS, CN982, CN983 NS, CN985, CN991 NS, CN996 NS, CN2920, CN8881 NS, CN8883 NS, CN9001 NS, CN9004, CN9005, CN9009, CN9011, CN9021 NS, CN9023, CN9028, CN9030, CN9178 NS, CN9290, CN9893 NS, CN929, CN989 NS, CN968 NS, CN9006 NS, CN9010, manufactured by Arkema Inc. NS, CN9025, CN9026, CN9039, CN9062, CN9110 NS, CN9029, CN8885 NS, CN9013 NS, CN973, CN978 NS, CN992, CN9167, CN9782, CN9783, CN970, CN971, CN972, CN975 NS, CN9165 etc. In addition, when the component (X) having a structural unit derived from butadiene described later contains a radical polymerizable monomer (X1) having a structural unit derived from butadiene, for example, TE2000 manufactured by Nippon Soda Co., Ltd. can be used as the urethane (meth)acrylate having a structural unit derived from butadiene.
[0029] The number average molecular weight of the urethane (meth)acrylate is preferably 1,000 or more, more preferably 1,500 or more, even more preferably 2,000 or more, and preferably 10,000 or less, more preferably 8,000 or less, even more preferably 5,000 or less. When the number average molecular weight of the urethane (meth)acrylate is within the above range, the number of moles of the polyol portion falls within an appropriate range, which further improves the flexibility of the adhesive composition and, in turn, the coatability thereof. The number average molecular weight of the urethane (meth)acrylate can be measured by gel permeation chromatography (GPC). For example, the following measurement conditions can be used for GPC. The number average molecular weight Mn of urethane (meth)acrylate is measured using GPC (Tosoh Corporation's "HLC-8120GPC") at a flow rate of 0.5 mL / min and a column oven temperature of 40°C using tetrahydrofuran (THF) as the solvent, polystyrene as the standard sample, and TSKgel super H1000+H2000+H3000 as the column.
[0030] The acrylic equivalent of the urethane (meth)acrylate is preferably 1000 or more, more preferably 1200 or more, even more preferably 1500 or more, and preferably 3000 or less, more preferably 2800 or less, even more preferably 2600 or less, even more preferably 2500 or less, even more preferably 2300 or less. When the acrylic equivalent of the urethane (meth)acrylate is within the above range, crosslinking groups in the radical polymerizable monomer (A) can be formed appropriately, and the flexibility of the resulting adhesive can be further improved. The acrylic equivalent of the urethane (meth)acrylate is given by the following formula (2). Acrylic equivalent: e = A / B (2) Where: A: Weight average molecular weight measured using size exclusion chromatography in terms of polystyrene B: Number of (meth)acrylate groups in one urethane (meth)acrylate molecule Shows.
[0031] The viscosity of the urethane (meth)acrylate is preferably 50 Pa·s or more, more preferably 75 Pa·s or more, even more preferably 100 Pa·s or more, preferably 125 Pa·s or more, and preferably 1000 Pa·s or less, more preferably 750 Pa·s or less, even more preferably 500 Pa·s or less, even more preferably 300 Pa·s or less. When the viscosity of the urethane (meth)acrylate is within the above range, the viscosity of the resulting adhesive composition can be set within an appropriate range, which in turn improves the coatability. The viscosity of the urethane (meth)acrylate is measured at 45° C. using a Brookfield viscometer.
[0032] The content of the urethane (meth)acrylate in the adhesive composition, relative to the content of the radical polymerizable monomer (A) taken as 100 parts by mass, is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and even more preferably 8 parts by mass or more, and is preferably 80 parts by mass or less, more preferably 75 parts by mass or less, even more preferably 70 parts by mass or less, even more preferably 65 parts by mass or less, even more preferably 60 parts by mass or less, even more preferably 55 parts by mass or less, even more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, even more preferably 25 parts by mass or less, and even more preferably 15 parts by mass or less. By making the content of the urethane (meth)acrylate equal to or more than the above lower limit, the coating property of the adhesive composition can be further improved. Also, by making the content of the urethane (meth)acrylate equal to or less than the above upper limit, the adhesive strength can be further improved in a short time when two inorganic members are bonded together. In addition, when the adhesive composition contains the elastomer (X2) described later, it may contain the elastomer (X2) without containing the urethane (meth)acrylate, which allows the flexibility of the cured product of the adhesive composition to be appropriate.
[0033] The total content of the urethane (meth)acrylate and the polyfunctional (meth)acrylate in the adhesive composition is preferably 40 parts by mass or more, more preferably 50 parts by mass or more, preferably 60 parts by mass or more, preferably 70 parts by mass or more, and preferably 90 parts by mass or less, more preferably 85 parts by mass or less, and even more preferably 80 parts by mass or less, when the content of the radical polymerizable monomer (A) is taken as 100 parts by mass. By having the total content of the urethane (meth)acrylate and the polyfunctional (meth)acrylate within the above range, the coatability of the adhesive composition is further improved, and when two inorganic members are bonded together, the adhesive strength can be further improved in a short period of time.
[0034] The radically polymerizable monomer (A) may include a highly polar monomer. The highly polar monomer is a polymerizable monomer having a polar functional group and a carbon-carbon double bond. The highly polar monomer may be a monofunctional monomer (a monomer having one carbon-carbon double bond) or a polyfunctional monomer (a monomer having multiple carbon-carbon double bonds), but is preferably a monofunctional monomer.
[0035] From the viewpoint of further improving the interaction with inorganic components, the polar functional group possessed by the highly polar monomer preferably contains one or more types selected from the group consisting of a carboxy group, a hydroxy group, and a phosphate group, more preferably contains one or more types selected from the group consisting of a carboxy group and a phosphate group, and even more preferably contains a carboxy group.
[0036] The highly polar monomer preferably contains one or more selected from the group consisting of (meth)acrylic acid, fumaric acid, maleic acid, fumaric anhydride, maleic anhydride, a monomer having a phosphoric acid group and a (meth)acryloyl group, and a hydroxyalkyl (meth)acrylate, more preferably contains one or more selected from the group consisting of (meth)acrylic acid and a monomer having a phosphoric acid group and a (meth)acryloyl group, further preferably contains (meth)acrylic acid, and further preferably contains methacrylic acid. This can further improve the interaction with the inorganic member, etc.
[0037] The content of the highly polar monomer in the adhesive composition, relative to the content of the radical polymerizable monomer (A) taken as 100 parts by mass, is preferably 1 part by mass or more, preferably 5 parts by mass or more, preferably 10 parts by mass or more, preferably 15 parts by mass or more, preferably 20 parts by mass or more, and preferably 50 parts by mass or less, more preferably 45 parts by mass or less, preferably 40 parts by mass or less, preferably 35 parts by mass or less, preferably 30 parts by mass or less. By setting the content of the highly polar monomer within the above range, the interaction with the inorganic member can be improved, and when two inorganic members are bonded together, the adhesive strength can be improved in a short period of time.
[0038] The content of the radical polymerizable monomer (A) in the adhesive composition is preferably 70 mass% or more, more preferably 75 mass% or more, even more preferably 80 mass% or more, even more preferably 85 mass% or more, even more preferably 90 mass% or more, even more preferably 93 mass% or more, and may be, for example, 99 mass% or less, or 98 mass% or less, based on the entire adhesive composition. When the content of the radical polymerizable monomer (A) is within the above range, the adhesive strength can be improved in a short time when two inorganic members are bonded together, and the physical properties of the resulting bonded structure can be improved.
[0039] As described above, when the component (X) having a structural unit derived from butadiene contains a radical polymerizable monomer (X1) having a structural unit derived from butadiene, the radical polymerizable monomer (X1) is included in the radical polymerizable monomer (A). When the component (X) having a structural unit derived from butadiene contains the radical polymerizable monomer (X1) having a structural unit derived from butadiene, the decrease in the curing rate is further suppressed, and therefore, when two inorganic members are bonded together, the adhesive strength can be further improved in a short period of time. In other words, the radical polymerizable monomer (X1) having a butadiene-derived structural unit is a component having a butadiene-derived structural unit among the components of the radical polymerizable monomer (A). Among the components of the radical polymerizable monomer (A), from the viewpoint of further improving the adhesive strength in a short time when two inorganic members are bonded, it is more preferable that one or more selected from the group consisting of urethane (meth)acrylate, polyfunctional (meth)acrylate, and highly polar monomer have a butadiene-derived structural unit, and from the viewpoint of further improving the flexibility of the cured product of the adhesive composition, it is even more preferable that the urethane (meth)acrylate has a butadiene-derived structural unit. The structural unit derived from butadiene may be contained at the terminal of each component in the radical polymerizable monomer (A) or may be contained in the main chain.
[0040] The number of structural units derived from butadiene in the radical polymerizable monomer (X1) is preferably 10 or more, more preferably 15 or more, even more preferably 20 or more, even more preferably 25 or more, even more preferably 30 or more, and is preferably 70 or less, more preferably 60 or less, even more preferably 55 or less, even more preferably 50 or less. By making the number of butadiene-derived structural units in the radical polymerizable monomer (X1) equal to or greater than the above lower limit, the adhesive strength can be improved in a short time when two inorganic members are bonded together, and the flexibility of the cured product can be improved. Also, by making the number of butadiene-derived structural units in the radical polymerizable monomer (X1) equal to or less than the above upper limit, the flexibility of the cured product of the adhesive composition can be set within a more appropriate range.
[0041] <Elastomer (X2)> As described above, the component (X) having structural units derived from butadiene may include an elastomer (X2) having structural units derived from butadiene. The elastomer (X2) preferably contains one or more selected from the group consisting of butadiene rubber, (meth)acrylonitrile-butadiene rubber, and styrene-butadiene rubber, and more preferably contains (meth)acrylonitrile-butadiene rubber. In the elastomer (X2), the portion having a structural unit derived from butadiene is also called a soft segment unit, and exhibits rubber elasticity. The component (X) having a structural unit derived from butadiene contains an elastomer (X2) having a structural unit derived from butadiene, which further suppresses the decrease in the curing rate, and when two inorganic members are bonded together, the adhesive strength can be further improved in a short period of time, and the flexibility of the cured product of the adhesive composition can be further improved.
[0042] The content of structural units derived from butadiene in the elastomer (X2) is preferably 30% by mass or more, more preferably 40% by mass or more, even more preferably 50% by mass or more, even more preferably 60% by mass or more, even more preferably 70% by mass or more, and preferably 95% by mass or less, more preferably 90% by mass or less, even more preferably 85% by mass or less. By making the content of the butadiene-derived structural unit in the elastomer (X2) equal to or higher than the lower limit, the adhesive strength can be improved in a short time when two inorganic members are bonded together, and the flexibility of the cured product of the adhesive composition can be improved. Also, by making the content of the butadiene-derived structural unit in the elastomer (X2) equal to or lower than the upper limit, the flexibility of the cured product of the adhesive composition can be set within a more appropriate range.
[0043] The content of the elastomer (X2) is preferably 1 mass% or more, more preferably 3 mass% or more, even more preferably 5 mass% or more, even more preferably 8 mass% or more, and is preferably 20 mass% or less, more preferably 18 mass% or less, even more preferably 15 mass% or less, even more preferably 13 mass% or less, even more preferably 10 mass% or less, based on the total adhesive composition. By having the content of the elastomer (X2) within the above range, when two inorganic members are bonded together, the adhesive strength can be improved in a short time, and the flexibility of the cured product of the adhesive composition can be improved.
[0044] In addition, the content of the elastomer (X2), when the total content of the radical polymerizable monomer (A) and the elastomer (X2) is taken as 100 parts by mass, is preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, and even more preferably 8 parts by mass or more, and is preferably 50 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 30 parts by mass or less, even more preferably 20 parts by mass or less, and even more preferably 15 parts by mass or less. When the content of the elastomer (X2) is within the above range, the adhesive strength can be improved in a short time when two inorganic members are bonded together, and the flexibility of the cured product of the adhesive composition can be improved.
[0045] <Polymerization initiator (B)> The adhesive composition of the present embodiment contains a polymerization initiator (B). The polymerization initiator (B) polymerizes the carbon-carbon double bonds of the radically polymerizable monomer (A), and when two inorganic members are bonded together, the adhesive strength can be improved in a short period of time.
[0046] The polymerization initiator (B) preferably contains a thermal radical polymerization initiator. From the viewpoint of further improving reactivity, the thermal radical polymerization initiator preferably contains an organic peroxide, more preferably contains one or more selected from the group consisting of cumene hydroperoxide, paramenthane hydroperoxide, tertiary butyl hydroperoxide, diisopropylbenzene dihydroperoxide, methyl ethyl ketone peroxide and tertiary butyl peroxybenzoate, and further preferably contains cumene hydroperoxide.
[0047] The content of the polymerization initiator (B) in the adhesive composition of this embodiment, relative to the content of the radical polymerizable monomer (A) being 100 parts by mass, is preferably 0.1 parts by mass or more, more preferably 0.5 parts by mass or more, even more preferably 1.0 parts by mass or more, even more preferably 1.5 parts by mass or more, even more preferably 2.0 parts by mass or more, and is preferably 20 parts by mass or less, more preferably 15 parts by mass or less, even more preferably 10 parts by mass or less, even more preferably 8 parts by mass or less, even more preferably 5 parts by mass or less, and even more preferably 3 parts by mass or less. When the content of the polymerization initiator (B) is within the above range, the crosslinking reaction after bonding two inorganic members proceeds appropriately, and when the two inorganic members are bonded, the adhesive strength can be further improved in a short period of time.
[0048] <Reducing Agent (C)> The adhesive composition of the present embodiment contains a reducing agent (C). The adhesive composition of the present embodiment can have further improved curability by using a polymerization initiator (B) and a reducing agent (C) in combination. The reducing agent (C) may be any reducing agent that reacts with the polymerization initiator (B) to generate radicals. The reducing agent (C) preferably contains one or more types selected from the group consisting of tertiary amines, thiourea derivatives, and transition metal salts, and more preferably contains one or two types selected from the group consisting of tertiary amines and transition metal salts.
[0049] Examples of the tertiary amine include one or more selected from the group consisting of triethylamine, tripropylamine, tributylamine, and N,N-dimethyl-p-toluidine. Examples of the thiourea derivative include one or more selected from the group consisting of 2-mercaptobenzimidazole, methylthiourea, dibutylthiourea, ethylenethiourea, acetyl-2-thiourea, benzoylthiourea, N,N-diphenylthiourea, N,N-diethylthiourea, N,N-dibutylthiourea, and tetramethylthiourea. Examples of the transition metal salt include one or more selected from the group consisting of cobalt naphthenate, copper naphthenate, vanadyl acetylacetonate, etc. More preferably, the transition metal salt includes vanadyl acetylacetonate.
[0050] The content of the reducing agent (C) in the adhesive composition of this embodiment, relative to the content of the radical polymerizable monomer (A) being 100 parts by mass, is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.25 parts by mass or more, even more preferably 0.5 parts by mass or more, even more preferably 0.6 parts by mass or more, and is preferably 10 parts by mass or less, more preferably 8 parts by mass or less, even more preferably 5 parts by mass or less, even more preferably 3 parts by mass or less, and even more preferably 1 part by mass or less. When the content of the reducing agent (C) is within the above range, the crosslinking reaction after bonding two inorganic members proceeds appropriately, and the adhesive strength can be further improved in a short period of time when the two inorganic members are bonded together.
[0051] The physical properties of the adhesive composition will now be described.
[0052] The adhesive composition of this embodiment was measured using a Brookfield viscometer at a temperature of 25° C. and a shear rate of 0.6 s -1 The viscosities of the first and second parts, measured by the above method, are each preferably 30 mPa·s or more, more preferably 50 mPa·s or more, even more preferably 100 mPa·s or more, even more preferably 150 mPa·s or more, even more preferably 250 mPa·s or more, even more preferably 350 mPa·s or more, and even more preferably 400 mPa·s or more, and are preferably 2000 mPa·s or less, more preferably 1800 mPa·s or less, even more preferably 1700 mPa·s or less, even more preferably 1600 mPa·s or less, even more preferably 1500 mPa·s or less, even more preferably 1300 mPa·s or less, even more preferably 1200 mPa·s or less, even more preferably 1100 mPa·s or less, and even more preferably 1000 mPa·s or less.
[0053] Using a B-type viscometer, the temperature was 25°C and the shear rate was 5.9 s -1 The viscosities of the first and second parts, measured by the above method, are each preferably 20 mPa·s or more, more preferably 30 mPa·s or more, even more preferably 40 mPa·s or more, even more preferably 50 mPa·s or more, even more preferably 100 mPa·s or more, even more preferably 300 mPa·s or more, even more preferably 400 mPa·s or more, and preferably 2000 mPa·s or less, more preferably 1800 mPa·s or less, even more preferably 1700 mPa·s or less, even more preferably 1600 mPa·s or less, even more preferably 1500 mPa·s or less, even more preferably 1300 mPa·s or less, even more preferably 1200 mPa·s or less, even more preferably 1100 mPa·s or less, and even more preferably 1000 mPa·s or less.
[0054] The above shear rate is 0.6s -1 and shear rate 5.9 s -1 By measuring the viscosity of the first and second agents within the above range, the applicability of the first and second agents when applied to an inorganic component is improved, which in turn improves the mixability after bonding two inorganic components together, and the adhesive strength can be improved in a short period of time when the inorganic components are bonded.
[0055] In the adhesive composition of this embodiment, the first agent and the second agent are each applied to two inorganic members, and one minute after application of the first agent, the two inorganic members are bonded together. The tensile shear strength T(1) is preferably 0.01 MPa or more, more preferably 0.02 MPa or more, even more preferably 0.03 MPa or more, even more preferably 0.04 MPa or more, even more preferably 0.05 MPa or more, even more preferably 0.10 MPa or more, even more preferably 0.13 MPa or more, even more preferably 0.15 MPa or more, even more preferably 0.18 MPa or more, even more preferably 0.21 MPa or more, even more preferably 0.25 MPa or more, and is preferably 2.0 MPa or less, more preferably 1.5 MPa or less. By having the tensile shear strength T(1) of the adhesive composition be equal to or greater than the lower limit, the time required from adhering the inorganic member to proceeding to the process of transporting and conveying the resulting bonded structure can be shortened, and in various processes involving the bonded structure, the time required from adhering to proceeding to the next process can be shortened. Furthermore, by having the tensile shear strength T(1) of the adhesive composition be equal to or less than the upper limit, the resulting cured product can be given appropriate flexibility, and the workability can be further improved when adhering and temporarily fixing the inorganic member and then completely fixing it with a caulking or the like. The tensile shear strength T(1) represents the measurement value for the adhesive composition after the first and second parts have been mixed.
[0056] The tensile shear strength T(1) of the adhesive composition is measured as follows. A 20 mm range from the end of a cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) with a width of 25 mm, length of 100 mm, and thickness of 1.6 mm is sandblasted with alumina of grain size F150 at a processing pressure of 0.4 MPa and a gun / cold-rolled steel plate distance of 3 cm, and the surface of the sandblasted area is washed with acetone and then left to stand at 23 ° C. for 30 minutes to prepare a test piece, and two of these test pieces are prepared. Next, the first agent of the adhesive composition is applied to the sandblasted area of one test piece to a thickness of 20 μm to prepare test piece 1, and the second agent is applied to the sandblasted area of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, one minute after applying the first agent, test piece 1 and test piece 2 are bonded together so that the bonded area is 25 mm x 12.5 mm, and the bonded area is clamped with two modern pinches, and test piece 1 is fixed in a vice. A modern pinch with a total length of 54 mm, spring material: 60, spring diameter: 1.2φ, and plate thickness of 0.36 mm can be used. Next, 20 seconds after bonding, the modern pinch is removed, and 30 seconds after bonding, a mechanical force gauge is used to pull test piece 2 at a tensile speed of 20 mm / min. The value on the mechanical force gauge is read, and this value is the tensile shear strength T(1) (MPa).
[0057] Furthermore, in the adhesive composition of this embodiment, the first agent and the second agent are each applied to two inorganic members, and 60 minutes after application of the first agent, the two inorganic members are bonded together. The tensile shear strength T(60) is preferably 0.01 MPa or more, more preferably 0.02 MPa or more, even more preferably 0.03 MPa or more, even more preferably 0.04 MPa or more, even more preferably 0.05 MPa or more, even more preferably 0.10 MPa or more, even more preferably 0.11 MPa or more, even more preferably 0.14 MPa or more, even more preferably 0.15 MPa or more, even more preferably 0.18 MPa or more, even more preferably 0.20 MPa or more, even more preferably 0.22 MPa or more, even more preferably 0.25 MPa or more, and preferably 2.0 MPa or less, more preferably 1.5 MPa or less. By having the tensile shear strength T(60) of the adhesive composition be equal to or greater than the lower limit, when the first and second parts of the adhesive composition are applied to two inorganic members, respectively, and then the two inorganic members are bonded together after being left for about 60 minutes, the adhesive strength can be improved in a short time. Furthermore, by having the tensile shear strength T(60) of the adhesive composition be equal to or less than the upper limit, the obtained cured product can be given an appropriate degree of flexibility, and the workability can be improved when the inorganic members are bonded and temporarily fixed, and then completely fixed with caulking or the like. The tensile shear strength T(60) is measured in the same manner as the tensile shear strength T(1) described above, except that test piece 1 and test piece 2 are bonded together 60 minutes after the application of the first agent. The tensile shear strength T(60) represents the measurement value for the adhesive composition after mixing the first and second parts.
[0058] <Two-drug type> The adhesive composition of the present embodiment is of a two-component type. A two-dose formulation is one in which two drugs are filled in separate containers and mixed immediately before use. In the adhesive composition of the present embodiment, the polymerization initiator (C) is preferably contained in the first agent, and the reducing agent (D) is preferably contained in the second agent. It is preferable to adjust the amount of each component in the first and second agents so that the adhesive composition after mixing the first and second agents contains each component within the preferred content ranges described above for each component in the adhesive composition.
[0059] <Method for producing adhesive composition> In producing the adhesive composition of the present embodiment, it is preferable to appropriately adjust the mixing order, mixing method, etc. of the respective components. In producing the adhesive composition of this embodiment, it is preferable to first thoroughly mix the radical polymerizable monomer (A) and the elastomer (X2). As shown in the examples below, it is preferable to thoroughly and uniformly mix the radical polymerizable monomer (A) and the elastomer (X2) at 50 to 80°C to obtain a mixture, and then add other components to the mixture and stir it. By doing so, it is considered that the radical polymerizable monomer (A) and the elastomer (X2) are thoroughly and uniformly mixed. The adhesive composition produced in this way tends to easily satisfy the above-mentioned characteristics such as tensile shear adhesive strength, compared to adhesive compositions obtained by other production methods.
[0060] The adhesive composition of the present embodiment is capable of bonding between inorganic members such as metals and magnets. More specifically, the adhesive composition of the present embodiment can be suitably used as an automotive adhesive used in the manufacture of automobiles, and can be more suitably used as an adhesive for motors, and can be even more suitably used as an adhesive for fixing between a magnet and a rotor (rotor), between a magnet and a stator (fixed part), and between the steel plates that form a rotor (rotor). The adhesive composition of the present embodiment can also be suitably used as an adhesive for fixing a magnet and a metal in a field magnet portion of a speaker.
[0061] [Adhesive structure] The bonded structure of the present embodiment is a bonded structure in which two or more inorganic members are bonded together, and contains a cured product of the adhesive composition of the present embodiment between the inorganic members. The adhesive structure of the present embodiment has two or more inorganic members bonded together using the adhesive composition of the present embodiment, and therefore when two inorganic members are bonded together, the adhesive strength can be further improved in a short period of time.
[0062] [Method of manufacturing bonded structure] The method for producing a bonded structure of the present embodiment includes a bonding step of bonding inorganic members together using the adhesive composition of the present embodiment described above to obtain a bonded structure. The bonding process may further include a step of applying a first agent to an inorganic member, a step of applying a second agent to an inorganic member, and a step of bonding the first agent-coated surface of the inorganic member to which the first agent has been applied and the second agent-coated surface of the inorganic member to which the second agent has been applied. The first and second parts can be applied to the inorganic member by using an inkjet or the like. The process of applying the first agent and the second agent to the inorganic member and the process of bonding the first agent-coated surface of the inorganic member coated with the first agent and the second agent-coated surface of the inorganic member coated with the second agent can be carried out at room temperature (23°C). By keeping the temperature at 15°C or higher, the adhesive strength is improved when the inorganic members are bonded in a short time. Also, by keeping the temperature at 30°C or lower, curing is not too fast when the inorganic members are bonded in a short time, improving workability. The method for producing a bonded structure of the present embodiment uses the adhesive composition of the present embodiment, and therefore can improve the adhesive strength when inorganic members are bonded together in a short time, thereby shortening the time from bonding to proceeding to a process of transporting or conveying the bonded structure, and also shortening the time from bonding to proceeding to the next process in various processes that handle the bonded structure. In addition, since the adhesive composition of the present embodiment contains a component (X) having a structural unit derived from butadiene, even if a time is provided between the step of applying the first agent to the inorganic member and the step of applying the second agent to the inorganic member and the step of bonding the first agent-coated surface of the inorganic member coated with the first agent and the second agent-coated surface of the inorganic member coated with the second agent, the inorganic members can be bonded in a short time after lamination, and the adhesive strength can also be improved. The time between the step of applying the first agent to the inorganic member and the step of applying the second agent to the inorganic member and the step of bonding the first agent-coated surface of the inorganic member coated with the first agent and the second agent-coated surface of the inorganic member coated with the second agent can be specifically 60 minutes or less. Within this time, the adhesive strength can be improved in a short time when bonding inorganic members coated with the first agent or the second agent.
[0063] Although the embodiments of the present invention have been described above, these are merely examples of the present invention, and various configurations other than those described above can be adopted. Furthermore, the present invention is not limited to the above-described embodiments, and modifications and improvements within the scope of the present invention are included in the present invention. EXAMPLES
[0064] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples.
[0065] The following materials were used for the adhesive composition. <Radical polymerizable monomer (A)> · Urethane (meth)acrylate 1: Aliphatic polyether urethane acrylate, acryloyl groups in one molecule: 2, number average molecular weight: 12,000, polyol: tetramethylene glycol, isocyanate: isophorone diisocyanate, hydroxy (meth)acrylate: 2-hydroxyethyl acrylate Urethane (meth)acrylate 2: 1,2-polybutadiene type methacrylate, TE2000, viscosity: 150 Pa·s, acrylic equivalent: 2000, methacryloyl groups per molecule: 2, number average molecular weight: 2,500, polyol: polyol having a 1,2-polybutadiene structure, isocyanate: toluene diisocyanate, hydroxy (meth)acrylate: 2-hydroxyethyl acrylate, manufactured by Nippon Soda Co., Ltd. Highly polar monomer 1: methacrylic acid, AM, manufactured by Mitsubishi Gas Chemical Co., Ltd. Multifunctional (meth)acrylate 1: Dipentaerythritol penta- and hexaacrylate, DPHA M402, manufactured by Toagosei Co., Ltd. Multifunctional (meth)acrylate 2: Trimethylolpropane trimethacrylate, TMPT-M, manufactured by Shin-Nakamura Chemical Co., Ltd. Monofunctional (meth)acrylate 1: Isobornyl methacrylate, IB-X Monofunctional (meth)acrylate 2: Methyl methacrylate, MMA, manufactured by Mitsubishi Chemical Corporation Monofunctional (meth)acrylate 3: 2-hydroxyethyl methacrylate, 2HEMA, manufactured by Nippon Shokubai Co., Ltd. Monofunctional (meth)acrylate 4: Dimethylacrylamide, DMAA, manufactured by KJ Chemicals Co., Ltd. Monofunctional (meth)acrylate 5: Diethylacrylamide, DEAA, manufactured by KJ Chemicals Co., Ltd. Monofunctional (meth)acrylate 6: acryloylmorpholine, ACMO, manufactured by KJ Chemicals Co., Ltd. N-vinyl-2-pyrrolidone, manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.
[0066] <Elastomer (X2)> Elastomer 1: Acrylonitrile-butadiene rubber, manufactured by JSR Corporation, N250SL (acrylonitrile content: 19.5% by mass, butadiene-derived structural unit content: 81% by mass) <Polymerization initiator (B)> Polymerization initiator 1: Cumene hydroperoxide, PH-80, NOF Corporation <Reducing Agent (C)> Reducing agent 1: Vanadyl acetylacetonate, VOAA2, manufactured by Shinko Chemical Industry Co., Ltd. Reducing agent 2: Triethylamine, manufactured by Tokyo Chemical Industry Co., Ltd.
[0067] <Examples 1 to 5 and Comparative Examples 1 to 7> The components were thoroughly mixed in the proportions (unit: parts by mass) shown in Tables 1 and 2 using a stirring device equipped with a stirring blade to prepare the first and second parts, respectively. In preparing the first and second agents, each component of the radical polymerizable monomer (A) was mixed thoroughly and uniformly at 50 to 80° C. to prepare a mixture. Next, other components were added to the mixture and stirred, and then the mixture was degassed to prepare the first and second agents, respectively. <Example 6> The components were thoroughly mixed in the proportions (unit: parts by mass) shown in Table 2 using a stirring device equipped with a stirring blade to prepare the first and second parts, respectively. In preparing the first and second agents, first, elastomer 1 was added to highly polar monomer 1 and thoroughly mixed at 50 to 80°C using a stirring device equipped with a stirring blade, and then polyfunctional (meth)acrylate 2 was added and further mixed to obtain a mixture. Next, other components were added to the mixture and stirred, and then the mixture was defoamed to prepare the first and second agents, respectively. The following evaluations were carried out using the first and second agents obtained in Examples 1 to 6 and Comparative Examples 1 to 7. The results are shown in Tables 1 and 2.
[0068] <Viscosity of urethane (meth)acrylate> The viscosity of the urethane (meth)acrylate 2 was measured at 45° C. using a Brookfield viscometer.
[0069] <Viscosity of adhesive composition> The first and second parts of the adhesive composition of each example were measured using a Brookfield viscometer (product name: RVDV2T, manufacturer: Brookfield) at a temperature of 25°C and a shear rate of 0.6 s -1 Similarly, the viscosity of each of the first and second parts of the adhesive composition of each example was measured at a temperature of 25° C. and a shear rate of 5.9 s -1 The viscosity was measured.
[0070] <Tensile shear strength> Using the first and second parts of the adhesive composition of each example, the tensile shear strength T(1) and the tensile shear strength T(60) were measured as follows. A 20 mm range from the end of a cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) with a width of 25 mm, length of 100 mm, and thickness of 1.6 mm was sandblasted using alumina with a grain size of F150 at a processing pressure of 0.4 MPa and a gun / cold-rolled steel plate distance of 3 cm, and the surface of the sandblasted area was washed with acetone and then left to stand at 23 ° C. for 30 minutes to prepare a test piece. Two test pieces were prepared. Next, the first agent of the adhesive composition of each example was applied to the sandblasted area of one test piece to a thickness of 20 μm to prepare test piece 1, and the second agent was applied to the sandblasted area of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, test piece 1 and test piece 2 were bonded together 1 minute after application of the first agent so that the adhesive area was 25 mm × 12.5 mm, and the adhesive joint was clamped with two modern pinches (total length 54 mm, spring material: 60, spring thickness: 1.2φ, plate thickness 0.36 mm, manufactured by Minamiki Seisakusho Co., Ltd.), and test piece 1 was fixed with a vice. Next, the modern pinches were removed 20 seconds after bonding, and 30 seconds after bonding, a mechanical force gauge (product name: FB-500N, manufacturer name: Imada) was used to read the value of the mechanical force gauge when test piece 2 was pulled by hand at a tensile speed of 20 mm / min, and this value was taken as the tensile shear strength T(1) (MPa). Further, the tensile shear strength T(60) (MPa) was measured in the same manner as above, except that the test pieces 1 and 2 were bonded together 60 minutes after the application of the first agent.
[0071] [Table 1]
[0072] [Table 2]
Claims
1. A two-part adhesive composition comprising: A method for producing a polymerization reaction system comprising: a radical polymerizable monomer (A); a polymerization initiator (B); and a reducing agent (C); the first agent contains the radical polymerizable monomer (A) and the polymerization initiator (B), the second agent contains the radical polymerizable monomer (A) and the reducing agent (C), The adhesive composition comprises a component (X) having a structural unit derived from butadiene.
2. 2. The adhesive composition according to claim 1, wherein the content of the component (X) is 1 part by mass or more and 80 parts by mass or less when the total amount of the adhesive composition is 100 parts by mass.
3. 3. The adhesive composition according to claim 1, wherein the component (X) comprises a radical polymerizable monomer (X1) having a structural unit derived from butadiene.
4. 4. The adhesive composition according to claim 3, wherein the number of the structural units derived from butadiene in the radical polymerizable monomer (X1) is 10 or more and 70 or less.
5. 3. The adhesive composition according to claim 1, wherein the component (X) comprises an elastomer (X2) having a structural unit derived from butadiene.
6. 6. The adhesive composition according to claim 5, wherein the elastomer (X2) comprises one or more elastomers selected from the group consisting of butadiene rubber, (meth)acrylonitrile-butadiene rubber, and styrene-butadiene rubber.
7. The adhesive composition according to claim 1 or 2, wherein the radical polymerizable monomer (A) comprises a urethane (meth)acrylate and a polyfunctional (meth)acrylate.
8. The adhesive composition according to claim 7 , wherein the urethane (meth)acrylate has structural units derived from the butadiene.
9. The adhesive composition according to claim 7 , wherein the polyfunctional (meth)acrylate has three or more (meth)acryloyl groups.
10. The adhesive composition according to claim 7 , wherein the content of the polyfunctional (meth)acrylate is 1 part by mass or more and 90 parts by mass or less when the content of the radical polymerizable monomer (A) is 100 parts by mass.
11. The adhesive composition according to claim 7 , wherein the urethane (meth)acrylate has two (meth)acryloyl groups.
12. The adhesive composition according to claim 7 , wherein the content of the urethane (meth)acrylate is 1 part by mass or more and 80 parts by mass or less when the content of the radical polymerizable monomer (A) is 100 parts by mass.
13. The adhesive composition according to claim 1 or 2, wherein the radical polymerizable monomer (A) comprises a highly polar monomer.
14. 14. The adhesive composition of claim 13, wherein the highly polar monomer comprises (meth)acrylic acid.
15. The adhesive composition according to claim 13, wherein the content of the highly polar monomer is 1 part by mass or more and 50 parts by mass or less when the content of the radical polymerizable monomer (A) is 100 parts by mass.
16. 3. The adhesive composition according to claim 1, wherein the content of the radical polymerizable monomer (A) is from 70% by mass to 99% by mass based on the total amount of the adhesive composition.
17. 3. The adhesive composition according to claim 1, wherein the content of the polymerization initiator (B) is 0.1 parts by mass or more and 20 parts by mass or less when the content of the radical polymerizable monomer (A) is 100 parts by mass.
18. 3. The adhesive composition according to claim 1, wherein the content of the reducing agent (C) is 0.01 parts by mass or more and 10 parts by mass or less when the content of the radical polymerizable monomer (A) is 100 parts by mass.
19. Using a Brookfield viscometer, the temperature was 25°C and the shear rate was 0.6 s -1 3. The adhesive composition according to claim 1, wherein the viscosity of the first part and the viscosity of the second part are each 30 mPa·s or more and 2000 mPa·s or less, as measured by a viscosity measuring method.
20. Using a Brookfield viscometer, the temperature was 25°C and the shear rate was 5.9 s -1 3. The adhesive composition according to claim 1, wherein the viscosity of the first part and the viscosity of the second part are each 20 mPa·s or more and 2000 mPa·s or less, as measured by a viscosity measuring method.
21. 3. The adhesive composition according to claim 1, which has a tensile shear strength T(1) of 0.01 MPa or more, as measured in accordance with the following <Tensile Shear Strength>. <Tensile shear strength> A range of 20 mm from the end of a cold-rolled steel plate (JIS G 3141:2017, SPCC-SD) having a width of 25 mm, a length of 100 mm, and a thickness of 1.6 mm is sandblasted using alumina having a grain size of F150 at a processing pressure of 0.4 MPa and a distance of 3 cm between the gun and the cold-rolled steel plate, and the surface of the sandblasted portion is washed with acetone and then left to stand for 30 minutes at 23° C. to prepare two test pieces. Next, the first agent of the adhesive composition is applied to the sandblasted portion of one of the test pieces to a thickness of 20 μm to prepare test piece 1, and the second agent is applied to the sandblasted portion of the other test piece to a thickness of 20 μm to prepare test piece 2. Next, the test piece 1 and the test piece 2 are bonded together one minute after application of the first agent so that the bonded area is 25 mm × 12.5 mm, the bonded portion is clamped with two modern pinches, and the test piece 1 is fixed in a vice. Next, the modern pinches are removed 20 seconds after bonding, and 30 seconds after bonding, the test piece 2 is pulled at a tensile speed of 20 mm / min using a mechanical force gauge, and the value of the mechanical force gauge is read, and this value is the tensile shear strength T (1) (MPa).
22. The adhesive composition according to claim 1 or 2, which is capable of bonding inorganic members to inorganic members.
23. An adhesive structure in which two or more inorganic members are adhered to each other, A bonded structure comprising the cured adhesive composition according to claim 1 between the inorganic members.
24. A method for producing a bonded structure, comprising the steps of: The adhesive composition is used to bond inorganic members to each other to obtain a bonded structure, The method for producing an adhesive structure, wherein the adhesive composition is the adhesive composition according to claim 1 or 2.
25. The bonding step includes: The method for manufacturing a bonded structure according to claim 24, further comprising a step of bonding a first agent-coated surface of the inorganic member to which the first agent has been coated and a second agent-coated surface of the inorganic member to which the second agent has been coated.
Citation Information
Patent Citations
Acrylic curable resin composition
JP2018172565A
Two-agent type acrylic adhesive composition, and joined body that is joined together using the same
JP2020026507A
Adhesive set and method for producing structure
JP2021024910A